Gambaran kadar bilirubin pasien tuberkulosis paru selama pengobatan di RSUP Prof. Dr. R. D. Kandou Manado periode Januari 2012 – Desember 2014 - Pontoh, Livinia G.; Polii, Efata B.I.; Gosal, Fandy (e-CliniC, 2016)
Abstract: Indonesia still ranks as the third country in the world to have the most cases of tuberculosis (TB). For this reason, there is a needed treatment for TB, called the Anti-Tuberculosis Drugs (ATD) which comprises of isoniazid, ethambutol, pyrazinamide, rifampicin and streptomycin and this should be taken for 6-8 months. However, ATD has side effects mainly in disturbing the liver function that can be assessed by the serum levels checkup of SGOT, SGPT and bilirubin. This study aimed to determine the level of bilirubin pulmonary TB of patients during the treatment in RSUP Prof. DR. R.D. Kandou Manado for the period of January 2012 to December 2014. This was an observational descriptive study with a cross sectional design by using the medical records of patients of pulmonary TB hospitalization for the period of January 2012 to December 2014. There were 32 patients as samples. There has been an increase in total bilirubin levels during the ATD treatment. It has been discovered that as big as (47%) had an increase level of total bilirubin. The total of bilirubin levels had increased more in male patients. The increase in the total bilirubin occurred in the age of >35 and the more it increases with age. Meanwhile, the increase in direct bilirubin levels had been found in as many as (56%). The indirect bilirubin levels had been found to be normal in (91%). A total of (31%), with hyperbilirubinemia, had not had comorbidities and most had often occurred in the first month of ATD treatment.Keywords: pulmonary tuberculosis, bilirubin, antituberculosis drug, hepatotoxicityAbstrak: Indonesia masih menempati urutan ketiga negara penderita tuberkulosis (TB) terbanyak didunia. Untuk itulah, dibutuhkan pengobatan TB, yang dinamakan Obat Anti Tuberkulosis (OAT) yang terdiri isoniazid, etambutol, pirazinamid, rifampicin dan streptomisin yang harus dikonsumsi selama 6-8 bulan. Akan tetapi, OAT memiliki efek samping terutama menggangu fungsi hati yang dapat dinilai melalui pemeriksaan kadar serum SGOT, SGPT dan bilirubin. Untuk mengetahui kadar bilirubin pasien TB Paru selama pengobatan di RSUP Prof DR. R.D. Kandou Manado periode Januari 2012-Desember 2014. Desain penelitian yang digunakan adalah penelitian observasional deskriptif dengan pendekatan potong lintang (cross sectional) dengan memanfaatkan rekam medik pasien TB Paru rawat inap periode Januari 2012-Desember 2014. Jumlah sampel yang terpakai sebanyak 32 orang. Terjadi peningkatan kadar bilirubin total selama pengobatan OAT. Ditemukan sebesar (47%) terjadi peningkatan kadar bilirubin total. Kadar bilirubin total meningkat lebih banyak pada pasien laki-laki. Peningkatan bilirubin total terjadi pada usia >35 tahun dan semakin meningkat seiring bertambahnya usia. Sedangkan, kadar bilirubin direk ditemukan sebanyak (56%) terjadi peningkatan kadar bilirubin direk. Kadar bilirubin indirek ditemukan normal pada (91%). Sebanyak (31%) yang menderita hiperbilirubinemia tidak memiliki penyakit penyerta dan paling sering terjadi pada satu bulan pertama pengobatan OAT.Kata kunci: tuberkulosis paru, bilirubin, obat antituberkulosis, hepatotoksitas